Eksplorasi Etnomatematika pada Kue Baruasa - S, Shahriani; Nur, Fitriani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
This study aims to explore the application of ethnomathematics concepts to the traditional Bugis-Makassar cake, Baruasa, especially in the context of geometry and the cultural values contained therein. Using an ethnographic approach, this study involves direct observation, interviews, and documentation to understand the cultural philosophy and local mathematical practices applied in the making and serving of the cake. The results show that the round shape and dense texture of Baruasa cake symbolize the values of togetherness, unity, and resilience. In addition, the process of making this cake contains geometric elements such as circles and squares, which are relevant for culture-based mathematics learning. This study contributes to preserving cultural heritage through a scientific approach and provides inspiration in integrating local culture into mathematics teaching.